Pengaruh Perhatian Orang Tua Terhadap Minat Belajar Siswa Kelas V di SD Negeri 023 Kecamatan Siabu Kabupaten Mandailing Natal - Desi Rani (Journal of Social and Policy Issues, 2021)
The student's interest can indicate the success of a learning activity. Because one of the factors influencing the success of learning activities is interest. External and internal factors, such as parental attention and the school environment, influence students' interest in learning. The researcher demonstrated in the study that the students' interest in learning class V SD Negeri 023 Siabu, Mandailing Natala Regency, was still constrained and had not reached the curriculum's maximum. The purpose of this study is to determine the effect of parental attention on student learning interest in class V SD 023 Siabu, Mandailing Natal Regency. This study employs a quantitative approach. By conducting interviews, distributing questionnaires, and documenting data. This study's sample size was 20 grade V students, and it was a population study because the sample size was less than 100. The research discussion focused on variables such as tutoring, parental advice, parental supervision, motivation, student attention, students' love and interest, and attention. (1) There is an effect of parental attention on student interest in learning, (2) There is no effect of parental attention on student interest in learning. The study's correlation analysis results show that parents promise that if their children are ranked, they will be rewarded, and parents teach about good learning procedures with results. Pearson Correlation.1000 ** and 000 0.05 And it was concluded that parental attention had an effect on and significance for the learning interest of Mandailing Natal Class V Sd 023 Siabu students in 2020-2021.